Sintering and rounding kinetics of irregular glass particles - Reis, Raphael M. C. V. (2018)
Compacts of irregular glass particles sinter up to five times faster than sphericalparticle compacts of the same composition. This effect has been attributed to the sharp edges of irregular particles. In this article, we propose and test a phenomenological model for the sintering kinetics of jagged glass particles considering their rounding during sintering. We assume that the small radii of curvature of the particle edges increase as the particles round off and control the sintering rate. We tested the model by measuring the sintering shrinkage of spherical and irregular particle compacts of a diopside (MgO·CaO·2SiO2) glass and using literature sintering data for particles of different shapes of a soda‐lime‐silica glass. The sintering rate of irregular‐particle compacts is initially much higher but tends to reach that of their spherical counterparts as they round off. Our model describes the experimental shrinkage of both glasses and explains the shrinkage anisotropy of irregular‐particle compacts in the initial stages of sintering, providing a significant step toward the understanding and description of the sintering kinetics of jagged glass particles.